Longitudinal Changes in CT Body Composition in Patients Undergoing Surgery for Colorectal Cancer and Associations With Peri-Operative Clinicopathological Characteristics - Dolan, Ross D.; Abbass, Tanvir; Sim, Wei M. J.; Almasaudi, Arwa S.; Dieu, Ly B.; Horgan, Paul G.; McSorley, Stephen T.; McMillan, Donald C. (Frontiers in Nutrition, 2021)
There is evidence that there is a direct association between body composition, the magnitude of the systemic inflammatory response and outcomes in patients with colorectal cancer. Patients with primary operable disease with and without follow up CT scans were examined in this study. CT scans were used to define the presence and changes in subcutaneous fat (SFI), visceral fat (VFA), skeletal muscle mass (SMI) and density (SMD). In total 804 patients had follow up scans and 83 patients did not. Furthermore, 783 (97%) patients with follow up scans and 60 (72%) of patients without follow up were alive at one year. Patients with follow-up scans, they were younger (p<0.001), had a lower ASA (p<0.01), underwent laparoscopic surgery (p<0.05), had a higher BMI (p<0.05), had a higher SMI (p<0.01), had a higher SMD (p<0.01) and better 1 year survival (p<0.001). Overall only 20% of patients showed changes in their SMI (n=161) and even less showed relative changes of 10% (n=82) or more. In conclusion over the period of approximately 12 months, low skeletal muscle mass was associated with the systemic inflammatory response and was largly maintained following surgical resection.